PENGARUH PERPUTARAN MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN FOOD AND BEVERAGE - Parso Parso; Nurdiyah Rafitasari (Institut Teknologi dan Bisnis Swadharma, 2021)
This study aims to determine the effect of working capital turnover, liquidity, and solvency on financial performance. In this study, the dependent variable used is Financial Performance by using the calculation of Return On Investment (ROI), while the independent variables in this study are Working Capital Turnover, Liquidity, and Solvency. This study uses quantitative research methods and the data used are secondary data, namely reports. annual finance. The population in this study was 18 Food and Beverage companies listed on the Indonesia Stock Exchange from 2013-2017. Sampling in this study using the purposive sampling technique. Based on the sampling technique above, the samples in this study are 7 Manufacturing companies in the Food and Beverage Sub-Sector. The data analysis technique started with descriptive statistical tests, then continued with panel data regression analysis, panel model selection method, classical assumption test consisting of regression normality test, heteroscedasticity, multicollinearity test, and autocorrelation test. Hypothesis test using multiple linear regression, t-test, F test, and coefficient of determination. The results of this study indicate that the correlation coefficient (R) is 0.628. This means that the relationship between the independent variable and the dependent variable is 62.8%. From these figures, it can be seen that the relationship between the independent variable and the dependent variable is strong. Adjusted R Square (????2) is 0.394, which means that the ability of the independent variable to explain the variation in the dependent variable is 39.4%, while the remaining 60.6% is explained by other factors outside the analyzed regression model